University teachers' self-reflection on their academic growth. Issue 3 (27th May 2017) - Pedrosa-de-Jesus, Helena; Guerra, Cecília; Watts, Mike
Abstract : This study followed the academic growth of four university teachers, over a two-year period, with the intention of enhancing inquiry-based learning in practice. Data were generated within the natural settings of classrooms, laboratories and lecture halls, through the analysis of teaching materials, low-participation observation, informal discussions and semi-formal interviews. The research approach was based on a critical social paradigm, assuming principles of action-research methodology privileging a transitional 'instructional coaching approach'. Outcomes show a marked interest in the design and development of innovative approaches to teaching, learning, feedback and assessment. They demonstrated strong collaborative practices, insightful reflections on their teaching activities, and willingness to share evaluations both within and without of university contexts and successfully contributing thoughts and ideas to a wider audience.